Adaptasi Bahasa Sunda dalam Al-Amin Al-Qur’an Tarjamahan Sunda: Menelusuri Interaksi Budaya dalam Proses Penerjemahan Al-Qur'an - Farhan, Rivki Lutfiya (Contemporary Quran, 2024)
This study examines the application of vernacularization in Al-Amin's translation of the Qur'an, aiming to understand how the adaptation of the Sundanese language influences the comprehension and reception of sacred texts within the local cultural context. The research focuses on the use of both buhun (ancient) and kiwari (modern) languages in the translation, with the goal of aligning the Qur'anic text with Sundanese cultural wisdom. Employing content analysis and Sally Engle Merry's theory of vernacularization, the study investigates how language adaptation reflects the interaction between the Qur'anic text and Sundanese culture. The findings indicate that Al-Amin's translation effectively integrates local cultural elements through the use of buhun language to preserve cultural identity and contemporary language to ensure relevance for modern readers. This balance between tradition and modernity facilitates greater understanding within the local community. Additionally, the research reveals that vernacularization not only addresses linguistic issues but also enhances the understanding of the sacred text by aligning its meaning with the social realities of Sundanese culture. This contributes significantly to translation and cultural interaction studies, demonstrating how Qur'anic translation can act as a bridge between source and target cultures and expand our understanding of how sacred texts are adapted to local contexts.